Introduction to biotechnology - P.R. Gilbert (2013)
Written primarily for undergraduate and postgraduate biotechnology and microbiology students, this book covers the basics as well as advanced topics on the subject.
Biotechnology, an overview -- Cells and organelles -- Chromosome and DNA replication -- Biomolecules -- Fundamentals of biochemical engineering -- Genetic engineering -- Genomics, proteomics, and bioinformatics -- Enzyme biotechnology -- Protein structure and engineering -- Microbial biotechnology -- Plant biotechnology -- Animal biotechnology -- Environmental biotechnology -- Horizon of biotechnology -- Bioethics and biosafety -- Intellectual property rights and biopatents.
Includes bibliographical references (pages [614]-617) and index.
Keywords: Biotechnology -- Textbooks; Chemical industry -- Technological innovations -- Textbooks